1996
DOI: 10.1063/1.872004
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulations of Nova high growth factor capsule implosion experiments

Abstract: Capsule implosion experiments carried out on the Nova laser [E. M. Campbell et al., Rev. Sci. Instrum. 57, 2101 (1986)] are simulated with the three-dimensional HYDRA radiation hydrodynamics code [NTIS Document No. DE-96004569 (M. M. Marinak et al. in UCRL-LR-105821-95-3)]. Simulations of ordered, near single mode perturbations indicate that structures which evolve into round spikes can penetrate farthest into the hot spot. Bubble-shaped perturbations can burn through the capsule shell fastest, in which case t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(69 citation statements)
references
References 29 publications
2
67
0
Order By: Relevance
“…Earlier studies of the growth rates of single perturbation modes have shown that the modes l•40 are responsible for most of the amplitude of the distortions in the interface [12]. The surface roughness and the bump on the capsule both are made up from many l-modes.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies of the growth rates of single perturbation modes have shown that the modes l•40 are responsible for most of the amplitude of the distortions in the interface [12]. The surface roughness and the bump on the capsule both are made up from many l-modes.…”
Section: Resultsmentioning
confidence: 99%
“…The goals of the hydrodynamics experiments were firstly to exercise x-ray backlighting capabilities on NIF, and secondly, to extend the study of hydrodynamic jets [41,42] to 3D and multjjet geometries for validating new 3D codes [43]. Figure 13 shows the experimental set-up.…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…Three dimensional radiation hydrodynamic simulations and experiments (Marinak 1996) show that for smooth capsules the neutron yield of high growth factors implosion on Nova should be the measured 30% of the calculated 1D yield for C, -12. The Omega laser has the capability of using 40 of its 60 beams into a hohlraum producing better symmetry than Nova (Decker et al 1998).…”
Section: The Scientific Basis Of the Nif Laser Systemmentioning
confidence: 99%